2019
DOI: 10.1007/s40846-019-00477-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mesh-Defect Removal Algorithm to Enhance the Fitting of 3D-Printed Parts for Comminuted Bone Fractures

Abstract: Purpose Mesh self-intersection defects and image noise may prevent 3D model reconstruction and mesh formation of bones with comminuted fractures, making it impossible to assemble 3D-printed fragments perfectly. This study proposes an algorithm to remove overlapping meshes and to smooth fracture surfaces in order to fabricate well-assembled 3D-printed bone. Methods 3D bone reconstruction, segmentation, and reduction were directly performed for three different classes of clinical fracture cases: pelvic 62-B1, 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We found that the scope of MI becomes increasingly interdisciplinary, particularly for mechanical engineering. With the increasing application of mechanical engineering in medical areas, using 3D printing technology to build surgical simulators for training and preoperative surgical rehearsal is of considerable interest to researchers [48,49]. In terms of research subdomains, research results in bioinformatics, nursing informatics, medical image informatics, clinical medicine and evidence-based medicine have been fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the scope of MI becomes increasingly interdisciplinary, particularly for mechanical engineering. With the increasing application of mechanical engineering in medical areas, using 3D printing technology to build surgical simulators for training and preoperative surgical rehearsal is of considerable interest to researchers [48,49]. In terms of research subdomains, research results in bioinformatics, nursing informatics, medical image informatics, clinical medicine and evidence-based medicine have been fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…The publication of these topics indicates the interdisciplinary nature of this scientific field. For example, 3D printing technology in surgical simulator construction for training and preoperative surgery practice has been researchers' focus (42,43). Feng also considered these as the main and emerging topics in the medical informatics field (17).…”
Section: Discussionmentioning
confidence: 99%
“…There were also different computing strategies proposed in boundary-based methods. For example, scale-space curvature matching based method, 7 mirror matching based method, 8,9 kernel correlation based method, 10 fracture line based method, 11,12 cluster trees based method, 13 matching point pair based method. 14 The boundary-based methods have achieved good results in registering broken bones with clear and similar boundaries.…”
Section: Related Workmentioning
confidence: 99%